Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Karanganyar - Dela Widyastuti; Maya Widyana Dwi; Indra Lila Kusuma (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This study aims to examine the influence of tax knowledge, taxpayer awareness, and tax sanctions on motor vehicle taxpayer compliance in Karanganyar Regency. The population in this study consisted of all motor vehicle taxpayers registered in Karanganyar Regency, totaling 380,349 taxpayers. This research employed a quantitative approach with a sample of 100 respondents selected using a random sampling technique. Primary data were collected through questionnaires and analyzed using descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, F-tests, t-tests, and coefficient of determination (R²) using SPSS 25. The results showed that tax knowledge and tax sanctions have a significant effect on motor vehicle taxpayer compliance, while taxpayer awareness does not have a significant effect on compliance. The coefficient of determination (R²) value of 39.6% indicates that the independent variables in this study explain 39.6% of the variation in taxpayer compliance, while the remaining percentage is influenced by other factors outside the research model. These findings highlight the importance of improving tax knowledge and implementing effective tax sanctions to encourage taxpayer compliance.